2014
DOI: 10.2166/wh.2014.129
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between water hardness and cardiovascular diseases in Mostar city, Bosnia and Herzegovina

Abstract: The aim of this study was to determine the association of cardiovascular disease (CVD) of selected human subjects with the hardness of water they consume. Laboratory testing of physical and chemical parameters of water were made using standardized methods: Standard Methods 19th edn, 1995 (APHA, AWWA & WEF, Washington, DC), and ISO 7888:1985, ISO 10523:1998. Pearson's chi-squared test was used for the statistical analysis of data, with the significance level of 0.05. The obtained data were analysed using the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…In addition, hypohydration increased the incidence and the prevalence of urinary system diseases [7,8,9,10]. A clear relationship between the hardness of water and cardiovascular diseases was also reported [11,12,13]. It is crucial to maintain optimal hydration in order to ensure the normal functions of human body.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hypohydration increased the incidence and the prevalence of urinary system diseases [7,8,9,10]. A clear relationship between the hardness of water and cardiovascular diseases was also reported [11,12,13]. It is crucial to maintain optimal hydration in order to ensure the normal functions of human body.…”
Section: Introductionmentioning
confidence: 99%
“…Research done in Bosnia and Herzegovina showed significant correlation between the prevalence of CVD in the population group who drink soft water (the value of the relative risk (RR) is 1.127) [28].…”
Section: Resultsmentioning
confidence: 99%
“…Mineral-rich water contains antioxidants that could protect against metabolic syndromes [24]. Hard water can also reduce the prevalence of cardiovascular diseases [25]. However, this type of association could not be considered because the KHNANES does not investigate water type or hardness.…”
Section: Discussionmentioning
confidence: 99%